Good for me : all about food in 32 bites - Burns, Marilyn; Clifford, Sandy (Boston : Little, Brown, 1978)
An informative look at food and what it does for us.
Booklist.
Wilson's Junior High School.
5.3
5-8
Keywords: Food -- Juvenile literature; Nutrition -- Juvenile literature; Food; Nutrition; Food; Nutrition